Analysis Efforts of the Forum Pembauran Kebangsaan (FPK) in Preventing Community Conflicts in West Kalimantan - Lulu Musyrafah; Herlan; Musa, Dahniar Th (Universitas Negeri Yogyakarta, 2026)
Background: West Kalimantan has a long history of ethnic and religious conflicts that continue to shape intergroup relations. The Forum Pembauran Kebangsaan (FPK) was established by the Ministry of Home Affairs to prevent social conflict and promote national integration in this highly plural society. Objectives: This study aims to analyze the activities, impacts, and challenges of the FPK in preventing community conflicts in West Kalimantan. Method: This research employs a qualitative approach combined with a literature-based method, drawing on interviews, books, journal articles, and other relevant scholarly sources. Data were analyzed through thematic analysis guided by Anthony Giddens' Structuration Theory. Result: The FPK has organized national dialogue seminars, focus group discussions (FGDs), and social media campaigns including a TikTok competition themed Bhinneka Tunggal Ika. While these activities raise awareness of diversity and tolerance, they predominantly reach participants who are already aware of such issues and fail to penetrate more vulnerable or conflict-prone communities. Limited funding, minimal women's participation, and absence of structured follow-up mechanisms further constrain the forum's effectiveness. Conclusion: FPK holds significant potential as a conflict prevention platform; however, it faces substantial internal and external challenges including financial dependency, limited grassroots reach, and inadequate monitoring. Sustainable peacebuilding requires strengthened community engagement, expanded inclusivity, and systematic translation of recommendations into concrete government policies.